Development of land based mobile mapping system using global positioning system and close range photogrammetric techniques - Wong, Tony Chee Siang (2006)
The development of Mobile Mapping System (MMS) is still at an initial stage in Malaysia. This research concentrates on georeferencing geographical and topographical features and updating a digital base map using digital cameras and Global Positioning System (GPS). This developed MMS integrates GPS as navigation sensor and Charge Coupled Device (CCD) camera as mapping sensor. The strength of this system is in the ability to georeference mapping sensor (i.e digital camera) by GPS. The acquired digital images are processed and referred to a common coordinate system using photogrammetric software known as PhotoModeler. The results from the software are exported to 2D coordinate transformation program to determine the geodetic position of the objects. The final outputs are the position of the topographic features such as road, road sign, bus stop and building. These topographical features are plotted in 1:10,000 scale digital base map